PENANGANAN PENGURANGAN JUMLAH DOWNTIME BERLEBIH DARI UNIT ABC 1 DENGAN PENDEKATAN LEAN MAINTENANCE PADA PT. XYZ - Prakoso, Aditya Hendi; Mahbubah, Nina Aini (SIGMA TEKNIKA, 2024)
PT. XYZ is a manufacturing company that operates in the field of fertilizer and non-fertilizer production with the aim of helping the country realize a food self-sufficiency program. It is known that PT. XYZ has problems with excessive machine downtime in its production process. Problems occur because there is repeated damage to the machine, activities that involve waste, so that the maintenance system on one machine has not been carried out optimally. The aim of this research is to analyze maintenance activities implemented in the Company and then minimize waste in maintenance activities using a lean maintenance approach. Downtime data collection was carried out in April 2024, then data processing was carried out using equipment effectiveness to see how effective the existing equipment was, then continued with Maintenance Value Stream Mapping (MVSM) to find out waste that occurred during the maintenance process, after the cause of the waste. is known, several suggested options are given to minimize the waste that occurs. From the implementation of the recommendations made, the machine equipment effectiveness value increased from 92% to 97%, the maintenance effectiveness value increased from 41.6% to 66.7%.